The effects of biochar-compost (biocom) on cadmium availability and green mustard (Brassica juncea) growth - Jemi, Joseph Gary; Abu Sari, Norazlina; Othman, Nur Maizatul Idayu; Ruslan, Nur Aziera; Masuri, Mohd Aizuddin (GADING Journal of Science and Technology, 2023)
Recently, as the result from resulting from various natural processes and industrial activities, the concentration of heavy metals commonly found in the soil such as cadmium has increased. However, the combination of biochar and compost (BioCom) as one of the potential methods for remediating the contaminated soil is not well defined. Therefore, a study was conducted to evaluate the responses of BioCom on cadmium availability and green mustard growth. Four randomly arranged treatments with four replications ranging from 0 to 40% application of biochar in combination with compost and cadmium (Cd) contaminated mineral soils were done in the glasshouse. Soil chemical properties, plant chlorophyll content, fresh weight, dry weight and root length were assessed after 30 days of planting. The data was analyzed with a one-way ANOVA applied at significant level of 95%. The Cd concentration in plant tissue decreased up to 87% with the application of 20% BioCom. The soil pH was found to be significantly higher soil amended with 40% BioCom as compared to the unamended soil. However, the addition of BioCom has no effects on the plant growth. The study suggests that the BioCom application has great potential in reducing the cadmium availability.